Evaluation theories of product definition method for a successful new product - Alli, Hassan (Universiti Putra Malaysia Press, 2018)
In this paper, The Product Definition Method is used to facilitate the product designer to establish successful product design characteristics. It presents a complete process to involve users in the product definition stage of the design process. The validation of this method is conducted through using one example of a very successful product as a case study. In addition, the in-depth study of sales performance through Correlation Test and Regression Analysis of its success. The result identified that The Product Definition Method is a systematic method as well as a decision making tool in order to involve the user in the design process and will assist them to develop the product design specifications. It also allows the product designer to verify the product quality and make decisions to contribute to its success.